The Repertorio Americano (1974-1983): first academic journal founded in the National University of Costa Rica - Ramírez, Marybel Soto (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The article presents findings of the third epoch of the Repertorio Americano initiated in 1974 when the journal and the valuable collection of Garcia Monge that was published from 1919 to 1958, happened to be a part of the intellectual undivided assets of a new Costa Rican university that was born with a typical politic and educational proposal. The National University of Costa Rica, developed as a Required University, promised to publish again American Repertoire as an organ of intellectual diffusion and academic link with projection latinamericanism. Methodologically the work file had allowed locating and compiling documents historicallegal and institutional to analyze the approach process, justification and negotiation for the assignment of intellectual property rights of the print in complement with the interviews with one of the members of the ad-hoc commission organizer of the University. To analyze the magazine as an object of study was employed to the functional analysis of the form. The results allow the conclusion that American Repertoire in the UNA was not a fortuitous event within the process of creation and management of the nascent university. There is a confluence of facts politic-cultural related to the role that assumed the Required University imbued with the Latin American thought of the 1970s. Finally, we point out the efforts of the first editorial board to define and organize American Repertory editorially as university magazine from the points of contact and difference from its predecessor with which maintains the idea l of bringing peoples to culture and education.